Comparison between Two Decades of Prevalence of Intestinal Parasitic Diseases and Risk Factors in a Brazilian Urban Centre - Alves de Oliveira Serra, Maria Aparecida; Chaves, Cristina de Souza; Branco Coêlho, Zirlane Castelo; de Castro Rodrigues, Naya Lúcia; Martins Vale, Josias; Teixeira, Maria Jânia; Oliveira, Francisco Josemar Alves de; Araújo, Márcio Flávio Moura de; Coelho, Ivo Castelo Branco (Interdisciplinary Perspectives on Infectious Diseases, 2015)
Objectives. This study’s objective was to compare the prevalence of intestinal parasites and associated risk factors in children in urban communities, in the Brazilian Northeast, between two decades. Methods. This quantitative transversal study consisted of a comparative analysis of two different samples: the first viewing the years 1992–1996 and the other through a coproepidemiological data survey undertaken in 2010-2011. Results. It was evidenced that there was a reduction of intestinal parasites and that there were improvements in the socioenvironmental conditions between the two decades evaluated. It was observed that, in the period 1992–1996, playing out in the streets was associated with a higher risk for acquiring intestinal parasites. Over the 2010-2011 period, the characteristics of more than five residents per household, houses with dirt floors, children who live in homes without piped water, and children who play out in the streets were associated with a higher risk of intestinal parasitic infection. Conclusion. The study showed a reduction of intestinal parasitic diseases to 23.8% in 2010-2011 from 81.3% in 1992–1996 and improvement of the social-sanitary conditions of the population between the decades analyzed.